The Effect of Brand Trust and Ease Of Use Shopee Application on Consumer Purchasing Decisions in Palembang City - Oktavia, Diana; Nataliani, Nataliani; Madeleine, Madeleine (Universitas Pamulang, 2024)
Purpose: The purpose of this study was to determine the effect of Brand Trust on consumer purchasing decisions in the Shopee application; To determine the effect of Ease of Use on consumer purchasing decisions in the Shopee application. Methods: This study uses a quantitative research approach using a causality / cause-and-effect research methodology to find evidence whether there is a cause-and-effect relationship between the independent and dependent variables. The population in this study were consumers who had made purchases at E-Commerce Shopee. The sample size used reached 100 respondents. The sampling technique uses a non-probability method with a purposive sampling approach with the following criteria: Having the Shopee application; Respondents with a minimum age of 17 years; Respondents have made purchases in the shopee application at least 2 times. Findings: The results in the study prove that Brand Trust and Ease Of Use have a positive and significant influence on consumer purchasing decisions in the Shopee application. Implication: The implication of the results of this study is the importance of building brand trust and making it easier to use the product (Application) to increase purchasing decisions.